2014
DOI: 10.1245/s10434-014-3542-8
|View full text |Cite
|
Sign up to set email alerts
|

Thyroidectomy as Primary Treatment Optimizes Body Mass Index in Patients with Hyperthyroidism

Abstract: Objective The purpose of this study was to determine how the timing of thyroidectomy influenced postoperative weight change. Methods We conducted a two institution study, identifying patients treated with total thyroidectomy for hyperthyroidism. Patients were classified as “early” if they were referred for surgery as the first treatment option or “delayed” if they were previously treated with radioactive iodine. Groups were compared with the student's t-test or Chi-squared test where appropriate. Results T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
7
0
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 45 publications
(60 reference statements)
1
7
0
2
Order By: Relevance
“…La mayoría de los trabajos que publican sobre tiroidectomías son series de bastantes pacientes, una de las series con mayor número de pacientes fue realizado por la de Miccoli 998 pacientes, Bauer con 683 pacientes, Gervasio 253 pacientes, Schneider con 216 pacientes, nuestra serie de 296 casos (1,4,5) .…”
Section: Discussionunclassified
See 1 more Smart Citation
“…La mayoría de los trabajos que publican sobre tiroidectomías son series de bastantes pacientes, una de las series con mayor número de pacientes fue realizado por la de Miccoli 998 pacientes, Bauer con 683 pacientes, Gervasio 253 pacientes, Schneider con 216 pacientes, nuestra serie de 296 casos (1,4,5) .…”
Section: Discussionunclassified
“…Entre los diferenciados se citan al carcinoma papilar, folicular y de células de Hurthle. Los indiferenciados son el medular y el anaplásico (5) .…”
Section: Introductionunclassified
“…Most patients treated with ATDs were not seen at our institution at their initial presentation with GD, and thus their pre-treatment BMIs were not available. However, previous research has suggested that the use of sequential treatment modalities in adults can result in continued weight gain compared with definitive treatment as a first line approach [ 8 ]. This question would be interesting to investigate in pediatric patients as well.…”
Section: Discussionmentioning
confidence: 99%
“…While TTE was negatively correlated with ∆BMI SDS in our subanalysis, the weakness of this association suggests that other factors should also be considered. Though some studies in adults show differences in BMI outcome by treatment modality [ 8 , 9 ], this has not been demonstrated consistently, and it is unknown whether these expectations can be extended to children. We found similar outcomes in our population when compared to reports from other centers [ 5 ].…”
Section: Discussionmentioning
confidence: 99%
“…Even though weight gain with increasing age is well known, prevention of any undesired weight gain could be important for the maintenance of well-being in most patients. Several studies have addressed this issue with a focus on outcomes of thyroidectomy in patients with hyperthyroidism [2,4,5]. Other studies compared outcomes of thyroidectomy in thyroid cancer patients compared to those with benign nodules [6][7][8].…”
Section: Introductionmentioning
confidence: 99%